О НЕКОТОРЫХ ПРИЧИНАХ И УСЛОВИЯХ, СПОСОБСТВУЮЩИХ СОВЕРШЕНИЮ ПРЕСТУПЛЕНИЙ НА СУДОХОДНОМ ТРАНСПОРТЕ В РЕСПУБЛИКЕ КАЗАХСТАН (Journal of actual problems of jurisprudence, 2019)
The B.A. Begaliev’s article "About some reasons and conditions, promoting completion of the crimes on navigable transport inRepublic Kazakhstan" author lit most sharp problems, appearing in the course of reluctances to criminal manifestations in considereddirection, as well as are given offers on optimization of preventive activity.